Empirical Correlations for the Swelling Pressure of Expansive Clays in the City of Barranquilla, Colombia (2017)
Swelling behavior of clays is of great importance for numerous engineering applications due to the prevalence of expansive clays around the world. Expansive clays are present in Mexico City, United States, Australia, Africa and South America, among others. In some cases, these types of clays could present swell pressure values greater than 400 kPa. In this technical note, correlation equations are developed to estimate the swell pressure of clays using laboratory tests performed on swelling clays in the city of Barranquilla, Colombia. Correlations are based on Atterberg limits and water content among other soil properties. Equations with statistically significant coefficients were selected and compared with equations found in the literature. Developed correlations evidenced that swell pressure decays quickly as water content increases. It was found that for the studied soils, Atterberg Limits did not present statistical significance in the estimation of swell pressure.